A nationwide population-based study of Escherichia coli bloodstream infections: incidence, antimicrobial resistance and mortality. (June 2022) - Feldman, Sarah F.; Temkin, Elizabeth; Wullfhart, Liat; Nutman, Amir; Schechner, Vered; Shitrit, Pnina; Shvartz, Racheli; Schwaber, Mitchell J.; Andremont, Antoine; Carmeli, Yehuda
Abstract: Objectives: Escherichia coli is the leading cause of bloodstream infection (BSI). The incidence of E. coli BSI caused by antibiotic-resistant strains is increasing. We aimed to describe the nationwide incidence and resistance profile of E. coli BSI in Israel and its impact on mortality, to compare E. coli BSI mortality with all-cause mortality, and community-onset with hospital-onset E. coli BSIs. Methods: We used mandatory BSI surveillance reports submitted by all Israeli hospitals to the Ministry of Health and the national death registry. All E. coli BSIs from 1 January 2018 to 31 December 31 2019 in patients aged 18 and over were included. Results: A total of 11 113 E. coli BSIs occurred in 10 218 patients; 85% (9012/10 583) were community onset. Median age was 76 (IQR 65–85), and 57% (6304/11 113) of cases occurred in women. The annual incidence was 92.5 per 100 000 population. Antibiotic resistance was frequent and significantly more common in hospital-onset than in community-onset BSI; 65% (1021/1571) vs. 45% (4049/9012) were multidrug-resistant (MDR) (p < 0.001). The case fatality rate (CFR) was higher following hospital-onset BSI than community-onset: 23% (276/1214) vs. 12% (926/7620) at 14 days, 31% (378/1214) vs. 16% (1244/7620) at 30 days, and 55% (418/766) vs. 34% (1645/4903) at 1 year (p < 0.001 for all comparisons). The 1-year CFR was 47% (1258/2707) for MDR vs. 28% (928/3281) for non-MDR (p < 0.001). The annual mortality rate was 31.0 per 100 000 population, comprising 4.2% (31.0/734.8) of all causes of deaths. Discussion: E. coli BSI carries a high burden, with a large proportion of MDR isolates, which are associated with increased incidence and CFR.